Implementasi Exploratory Data Analysis (EDA) Untuk Menganalisis Berbagai Faktor Risiko Penyakit Jantung Di Amerika Serikat - Patricia, Sherly; Marpaung, Christopher Parulian; Wijaya, Lucky Raffael; Paramartha, Manisha Arie; Atmadja, Willyanto Dharmansyah; Ningsih, Rahmi Yulia (Journal of Student Development Information System (JoSDIS), 2023)
Heart disease is still a serious health problem, especially in the United States. The data shows that heart disease as one of the primary causes of death in the United States. Several health factors are known to be the risk factors for heart disease. Therefore, this study aims to analyze the relationship between several risk factors for heart disease in the United States that will being presented based on the results of the implementation of Exploratory Data Analysis (EDA) using the Python programming language. The method used in this research is quantitative research. This method used to present the results of EDA implementation in the form of visualization and analysis related to the dataset about the risk factors for heart disease in the United States. The results showed that all health factors contained in the dataset gave expected results, except drinking alcohol, have a specific influence on the risk of heart disease. In addition, the conclusion shows that stroke is the factor that has the highest impact on the occurrence of heart disease.